IMPACT OF WATER SALINITY (SODIUM AND SULFATE) ON DAIRY CATTLE AND ITS RELATION WITH OXIDATIVE STRESS IN BASRAH PROVINCE - Nameer A. khudhair; Nadhem M.J. Ali; Mgharab M.J. Al-Iedane (Basrah Journal of Veterinary Research)
Water salinity represents the most difficult challenge facing the livestock in Basrah province,therefore, twelve dairy cattle obtained from Farm of College of veterinary Medicine \Universityof Basrah. These animals were included and administrated salt water for 60 days with regularfeed supplementation and then administrated pure water(R-O) for another 60 days. All clinicalsigns were recorded during the study period and the blood sample was collected from cows inboth cases. Sodium, Sulphur and total antioxidant capacity values were measured. Four milkingcows were dead during the period of study as a result of high water salinity. Serum sodium andsulfate values were rise significantly when compared with the period of drinking pure waterwhile the effectiveness of total antioxidant capacity significantly decreased in dairy cows drinksalt water. This study investigated the deleterious effect of sodium and sulfate rises on total antioxidantcapacity in dairy cows.